ANALISIS TINGKAT KEBANGKRUTAN DENGAN MENGGUNAKAN METODE ALTMAN Z – SCORE PADA PERUSAHAAN ROKOK YANG TERDAFTAR DI BEI - Septiana, A. Rina (Program Studi Manajemen Fakultas Ekonomi dan Bisnis, 2022)
This study aims to determine the level of bankruptcy in Cigarette Companies Listed on the Indonesia Stock Exchange (IDX) using the Altman Z-Score Method. The data used is secondary data obtained by using documentation techniques. The population in this study were all cigarette companies listed on the Indonesia Stock Exchange for the 2016-2020 period. So that the samples used in this study were PT Gudang Garam Tbk, PT HM Sampoerna Tbk, PT Wismilak Inti Makmur Tbk, and PT Bentoel Internasional Investama Tbk. The data analysis technique used is descriptive analysis which provides an overview of the financial performance condition of the Cigarette Company based on the resulting financial statements. The results of this study indicate that there are three companies that are predicted to be in the category of not bankrupt or healthy within a period of five years, namely PT. Gudang Garam Tbk, PT. HM Sampoerna Tbk, and PT. Wismilak Inti Makmur Tbk. While PT. Bentoel Internasional Investama Tbk, only in 2016 was categorized in a healthy condition. Meanwhile, in 2017-2020 the company is predicted to be in a gray area condition.